A new record of the Blackish Oystercatcher, Haematopus ater ater (Vieillot and Oudart, 1825), in the Gulf of Guayaquil, Ecuador - Fernando Félix; Ben Haase (Check List, 2016)
We report a record of a single individual of the Blackish Oystercatcher, Haematopus ater ater (Vieillot and Oudart, 1825), photographed on 7 February 2015 in the Gulf of Guayaquil, Ecuador (02.73° S, 080.22° W). This species regularly occurs along rocky sea coasts, mainly in cold and temperate areas of South America. The record was observed during the warmest season and when an ongoing ENSO event in the Southeast Pacific has been confirmed. We discuss two potential causes for this unusual record: variability of environment conditions and population expansion from the Peruvian population.